(untitled) (Physical Education, Health and Social Sciences, 2025)
Although governmental and non-governmental rehabilitation programs have been in place since decades, the issue of street children in Pakistan continues to be a pertinent child protection and social justice issue to date. It is estimated that there are 1.5-2 million children in the streets working or living in them and this is a sign of long-term structural inequalities that comprise poverty, high urbanization rates, ineffective social protection frames, and poor child welfare governance. Research Objectives of this study are: To study the structural factors (e.g., poverty, urban marginalization, educational exclusion, child protection gaps) that facilitate the involvement of the streets and make the reintegration of street children in Pakistan impossible. To evaluate the psychosocial weaknesses such as trauma exposure, stigma, mental health issues, and interrupted family relations which influence the outcome of rehabilitation and sustainable reintegration. To measure the efficacy of current governmental and non-governmental rehabilitation and reintegration in fostering long-term social incorporation, educational continuity, and psychosocial prosperity of the street-linked children. To recommend a unified, trafficum, and rights-based, trauma-informed social work model in respect of sustainable rehabilitation and reintegration of street children in the Pakistani socio-cultural and policy environment. The research design chosen in this study was a qualitative research design to investigate structural barriers and psychosocial vulnerability to the reintegration of Pakistani street children. The research has been carried out in the selected cities in Pakistan where street children were very visible and where there were rehabilitation services. The target population consisted of children attached to the streets, social workers, the NGO employees, and child protection authorities. Participants having first hand experience of street involvement and reintegration were selected through purposive sampling. A sample of about 20-25 interviewees was taken until the data was saturated. Semi-structured interviews, focus group discussion and key informant interview were used to collect data. Thematic analysis was used to analyze the data through systematic procedures of coding. The first procedure was open coding in which frequently occurring ideas were identified after which they were grouped into broad themes.